IMPACT OF THE PROTAGONIST'S DEPRESSION IN JAY ASHER’S NOVEL THIRTEEN REASONS WHY - Putri, Nada Febriansyah; Wulan, Sri (JOURNAL OF LANGUAGE, 2024)
This study delves into an analysis of depression portrayed in Jay Asher's novel Thirteen Reasons Why, with a focus on the protagonist, Hannah Baker. The aims of this study are twofold: to discern the type of depression experienced by the protagonist and to elucidate the impacts of this depression as depicted in the novel. Employing a qualitative descriptive method, the analysis seeks to vividly describe and interpret the subject matter. The findings of this study reveal that the protagonist's depression falls within the category of severe depression, characterized by symptoms such as suicidal thoughts and actions. Furthermore, the analysis uncovers several impacts of the depression, including self-blame, feelings of inferiority, and persistent thoughts of death. The protagonist harbors self-reproach for negative events affecting her life and others, while also grappling with feelings of inferiority stemming from instances of bullying, betrayal, rape, and other traumatic experiences that mar her reputation. These experiences ultimately contribute to her belief that death is an escape from her overwhelming depression. By shedding light on the depiction of mental health, specifically depression, in this literary work, this study provides valuable insights. In conclusion, it underscores the importance of recognizing and addressing severe depression and its profound impacts.